1979
DOI: 10.1002/aic.690250520
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical power requirements of gas‐liquid agitated systems

Abstract: The power requirements for mechanical agitation of liquids have been investigated extensively, since this parameter is an important criterion for scaling-up stirred reactors, and it also relates to the overall mass transfer coefficient. There is only a limited number of useful correlations for its estimation such as those of Oyama and mechanical power input in nonaerated, agitated non-Newtonian liquids in a turbulent regime also varied with i V as indicated by Calderbank and Moo-Young (1959). It could thus be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“… 23. shows that the variation of the power number with impeller speed is similar in the 0.57 and 1.5 m i.d.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“… 23. shows that the variation of the power number with impeller speed is similar in the 0.57 and 1.5 m i.d.…”
mentioning
confidence: 82%
“…vessels, respectively, which are lower thaii those observed by Mihel and Miller [22], Luong and Volesk! [23], Hassan and Robinson [lo] and Hughmark [24]. These investigators determined the exponent as -0.24, -0.38, -0.38, and -0.25, respectively.…”
Section: Effect Of Vessel Sizementioning
confidence: 99%
“…Although Koloini et al (1989) reported that Hughmark's correlation predicted higher values for power input compared to their experimental data, in the case of the miniature bioreactor this correlation also slightly under estimates the power input compared to the measured values, especially at higher stirrer speeds. Finally the Luong and Volesky (1979) correlation based on the use of dimension- Table I. Summary of the most commonly reported gassed to un-gassed power consumption correlations ( P g /P ug ) for smaller scale stirred vessels Hughmark (1980) 0.16-1 Flat blade turbine 1 0.33 less groups and Newtonian fluids, is seen to greatly over predict the measured values and is unsuitable.…”
Section: Correlation Of Miniature Bioreactor Energy Dissipation Ratesmentioning
confidence: 94%
“…The values determined for the constants C, a, and b from Equation (7) were 0.22, 0.35, and 0.52 respectively as shown in Table II. Cui et al (1996); (^) Luong and Volesky (1979); (*) Mockel et al (1990). Experimental measurements as shown in Figure 2.…”
Section: Correlation Of Miniature Bioreactor K L a Valuesmentioning
confidence: 98%
“…Such modifications included taking into account the number and type of impellers and reactor dimensions, among others. 99,100,101 Along with the use of predictive correlations, power consumption may be determined experimentally through the use of electrical or calorimetric measurements, or through the use of dynamometers, torquemeters and strain gauges. 87 In bench-and pilot-scale bioreactors typically used for the fermentation of bacteria and fungal micro-organisms, the power consumption ranges from 1 to 3 kW m −3 .…”
Section: Scale-up Based On Volumetric Power Consumptionmentioning
confidence: 99%